2021
DOI: 10.1111/joa.13577
|View full text |Cite
|
Sign up to set email alerts
|

Río‐Hortega's drawings revisited with fluorescent protein defines a cytoplasm‐filled channel system of CNS myelin

Abstract: A century ago this year, Pío del Río‐Hortega (1921) coined the term ‘oligodendroglia’ for the ‘interfascicular glia’ with very few processes, launching an extensive discovery effort on his new cell type. One hundred years later, we review his original contributions to our understanding of the system of cytoplasmic channels within myelin in the context of what we observe today using light and electron microscopy of genetically encoded fluorescent reporters and immunostaining. We use the term myelinic channel sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 69 publications
2
15
0
Order By: Relevance
“…Rudolf Virchow initially designated the term “myelin” in 1854, named after the Greek word “marrow” (myelos), since it is especially plentiful in the brain’s center, or marrow [ 6 ]. He posited that neurons produced myelin, but Pío del Río Hortega’s better histological staining processes almost a century ago revealed that myelin is created by specific glial cells, which are OLs [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rudolf Virchow initially designated the term “myelin” in 1854, named after the Greek word “marrow” (myelos), since it is especially plentiful in the brain’s center, or marrow [ 6 ]. He posited that neurons produced myelin, but Pío del Río Hortega’s better histological staining processes almost a century ago revealed that myelin is created by specific glial cells, which are OLs [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this preprint (which this version posted July 10, 2022. ; https://doi.org/10.1101/2022.07.08.498895 doi: bioRxiv preprint receptor (SNARE) complexes, where vesicular SNARE proteins (v-SNAREs) pair with their cognate SNARE partners on the target membrane to trigger exocytosis. In myelin, vesicles have been observed in the inner tongue and are thought to travel through "myelinic channels" extending through compact myelin regions 5,6,[18][19][20] , but the molecular components and function of these vesicles are unclear. Previous studies reported the upregulation of v-SNARE isoforms VAMP3 and VAMP7 in myelinating oligodendrocytes 21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…Each myelin sheath is a continuous extension of the oligodendrocyte plasma membrane, and a single oligodendrocyte has been estimated to increase its membrane area by several thousand-fold 4 , requiring extensive addition of new membrane. Myelin sheaths are thought to grow in thickness and length by extending their innermost layer, or inner tongue, around and along the axon 5,6 , but the cellular machinery that adds new membrane to power myelination is unknown. Beyond developmental myelination, experience and learning during adulthood can induce oligodendrocytes to form new myelin or restructure existing myelin sheaths, adapting myelination patterns to altered neural circuitry and potentially accelerating regeneration after demyelination [7][8][9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Unpaired two-tailed Welch's t test. c, Clinical EAE scoring(1)(2)(3)(4)(5)(6)(7)(8)(9)(10) shows an ameliorated disease course in hMbp mice compared to wildtype controls. n Ctrl EAE = 13, n hMbp EAE = 10.…”
mentioning
confidence: 99%
“…Despite this, and based on the assumption that de-and amyelinated axons are especially vulnerable to injury, initial damage in MS is proposed to occur at areas naturally devoid of myelin, such as nodes of Ranvier [4][5][6] . We and others hypothesized that oligodendrocytes provide trophic support to axons [7][8][9] because axons are isolated from extracellular glucose at least in part by myelin itself 10 . Consequently, fully myelinated axons should be most dependent on oligodendrocytemediated metabolic support, which, in turn, would make myelinated axons most vulnerable to autoimmune attacks that impact the oligodendrocyte's capacity to support the myelinated axon.…”
mentioning
confidence: 99%